524 Cytodifferentiation of Pituitary Tumors Influences Pathogenesis and Cavernous Sinus Invasion. (April 2023) - Asmaro, Karam Paul; Zhang, Michael; Rodrigues, Adrian; Mohyeldin, Ahmed; Vigo, Vera; Vogel, Hannes; Born, Donald; Katznelson, Laurence; Fernandez-Miranda, Juan Carlos
Abstract : INTRODUCTION: Pituitary neuroendocrine tumors (PitNET) continue to offer unique challenges given their proximity to the cavernous sinus, whereby invasive behavior can dictate extent of resection and surgical outcome, especially in neuroendocrine-active tumors. Recent advances in surgical techniques have resulted in the development of transcavernous endonasal surgery for invasive tumors. METHODS: 169 consecutive primary PitNET were analyzed, of which 45% were neuroendocrine-active. There were 64 PIT-1, 62 SF-1, 38 TPIT, and 5 none-staining PitNets. The gold standard for cavernous sinus invasion was based on histopathological examination of the cavernous sinus medial wall and intraoperative exploration of cavernous sinus compartments. RESULTS: Cavernous sinus disease was present in 33% of patients. PIT-1 tumors had a significantly higher predilection for cavernous sinus invasion, 53% versus 24% and 18% for TPIT and SF-1 tumors, respectively (OR 6.13, 95% CI 1.08-2.58; p<0.001). For Knosp 0-2 tumors, 44% of PIT-1 tumors had cavernous sinus invasion compared to 7% and 13% for TPIT and SF-1 tumors, respectively (p < 0.01). Utilizing the transcavernous approach, surgical biochemical remission rates for patients with acromegaly, hyperprolactinemia, and Cushing's disease were 88%, 87%, and 94%, respectively. Granulation pattern of PIT-1 tumors, corticotroph functional status, and Crooke's cell corticotroph morphology did not influence cavernous sinus invasion. CONCLUSIONS: Likelihood of cavernous sinus invasion differed by transcription factor expression; PIT-1 expressing somatotroph and lactotroph tumors had a higher predilection for invading the cavernous sinus compared to other tumor subtypes. This elucidates a unique cavernoinvasive behavior absent in cells from other lineages. Innovative surgical techniques, however, can mitigate tumor behavior and achieve robust, reproducible biochemical remission and gross total resection rates. These findings can have considerable implications on the surgical management and study of PitNET biology and behavior.